Evaluation of retinal nerve fibre layer, optic nerve head, and macular ganglion cell analysis measurements for early glaucoma detection using spectral domain optical coherence tomography - Bhardwaj, Rahul; Sharma, Sandeep; Gaur, Rachana; Singh, Sindhuja; Chaudhary, Prakhar; Sain, Monika; Zaidi, Sayed Abbas Ali; Khan, Gayasuddin (International Journal of Research in Medical Sciences, 2020)
Background: Glaucoma is the leading cause of irreversible blindness worldwide. It is very important to diagnose glaucoma in early stages so that timely management can be done. Spectral domain optical coherence tomography (SD-OCT), is a newer device which helps to diagnose glaucoma early. The aim of our study was to evaluate the RNFL, ONH, and mGCA (GCL+IPL) measurements for early glaucoma detection using spectral domain optical coherence tomography (SD-OCT). Methods: Total 30, POAG (primary open angle glaucoma) suspects were compared with 30 normal controls. The Cirrus HD-OCT optic disc cube 200 × 200 protocol was used to measure ONH, RNFL and macular parameters. Results: The average cpRNFL thickness of all quadrants was significantly lower in POAG suspects, (84.13±7.42 μm versus 103.85±8.95 μm, p<0.001). The superior GCL+IPL thickness of POAG suspects and controls was 75.75±2.60 μm and 80.05±1.74 μm, respectively, (p<0.001). The inferior GCL+IPL thickness of POAG suspects and controls was 75.98±2.59 μm and 80.00±1.79 μm, respectively, (p<0.001). Conclusions: The SD-OCT is an important device to diagnose POAG suspects, early. The GCA measurements and average RNFL (especially superior and inferior) measurements, both are equally good to discriminate between glaucoma suspects and normal controls.